The development of online house rental and advertising system - Norjihan, A. G.; Chew, T. H. (2005)
Online House Rental Advertising System or OHRAS is an online system where house owner can post the advertisement of their house and house seeker can search for the house that meet their requirement. In a conventional method, house seeker has to advertise their house using newspapers.In this OHRAS, house owner can post their house advertisement via online.This project focuses on managing the advertising for house in Malaysia only.It is develop to solve the problems that arise from the traditional method of house advertising.OHRAS enable users to search a house that meet their requirement in various manners; by state or city, by rental rate or by types of house and other.It makes the searching process easier and flexible with three methods of searching; by browsing by state and city/district, quick search and advanced search.OHRAS has been developed using Cold Fusion as server-side programming language and Microsoft SQL Server 7 as for database management system.Using OHRAS, it makes out searching time more efficient and easier for us.It has been tested and being modified to get further enhancement.